READING THE SYMBOLS IN RUMI’S THE PHILOSOPHER AND THE SKIPPER - Dedi Irwansyah (Literature and Literacy, 2024)
While Sufi literature is believed to be a powerful instrument in introducing a model of spiritual journey, the symbols in such type of literature are not always easy to digest. This paper aims to contribute to our understanding of the mystical content of Sufi literature with a particular focus on the symbolism representing the Sufism spiritual journey seen in a Sufi literary text written by Jalaluddin Rumi. This study was conducted using a semiotic approach as it embraces symbolism under its study area. Data are drawn from Rumi’s “The Philosopher and The Skipper”, a short story in a book titled “Tales from the Land of the Sufis”. Data are analyzed qualitatively ranging from collecting the data through a careful reading to coding the text for description. The findings reveal that the four main stages of the spiritual journey are consecutively symbolized by ship (shari’a), swimming (tariqah), ocean (ma’rifat), and a gift (haqiqat). Other supporting symbols include ‘Ali (salik and sublime spiritual position), philosopher (human intellect), Sam (murshid), sea voyage (suluk), the sailors (tariqah members), the skipper (khalifah), a small island (zawiyah), and empty object (zuhud). It is argued that effective and meaningful exploration of symbolism in Sufi literature might be best done through a semiotic approach.